Travelling wave fault location in rural radial distribution networks to reduce wild fire risk - Jahromi, A.; Wolfs, P.; Islam, Syed (2015)
This paper introduces a new fault location algorithm for radial MV distribution networks employing distributed travelling wave observers. Incipient fault location may reduce the risk of wild or bush fire ignition by faulty MV overhead lines. Some faults can develop over time and may exist for an extended period before the right weather conditions result in a fire. Developing faults will produce travelling voltage waves. The distributed observers are synchronized by global positioning system and use the arrival time differences to locate faults. Modal and wavelet transformation is used to detect and time stamp the travelling wave arrival time by observers. The paper first provides a brief review of fault location technology then describes the Floyd-Warshell algorithm to calculate point to point distance matrix. A travelling wave detection methods and finally the fault location algorithm will be described. Simulation model is developed in EMTP-RV software to illustrate the performance of proposed algorithm based on real network data.